Health Locus of Control Terhadap Kepatuhan Minum Obat Pada Penderita Hipertensi - Rofiqi, Erfan; Lidyawati, Winda; Agung Wijaya, Siswanto (Jurnal Keperawatan Muhammadiyah, 2024)
Introduction: hypertension is a condition where blood pressure increases above normal limits. Hypertension is currently an exceptionally critical health problem known as the silent killer. One factor that can influence hypertension sufferers is compliance with diet and medication. Objective: This study aims to analyze the relationship between health locus of control and medication compliance. Method: The method used is a correlation analytical design with a cross-sectional approach. Data collection used a questionnaire with a total sample of 74 respondents. Analyze the data using Spearman rho statistics (α <0.05). Results: there was a relationship between hloc and and adherence to taking hypertension medication (ρ=0.002). Discussion: Based on the results. The presence of Hloc has a significant impact on medication complience. Therefore, it is necessary to strengthen the factors in blood pressure control, one of which is Hloc. So that compliance medication can improve